Engineering mechanics : Dynamics - Meriam, J. L.; Kraige, L. G. (Singapore: John Wiley & Sons, 2004)
Known for its accuracy, clarity, and applications, Meriam & Kraige's Engineering Mechanics: Dynamics has provided a solid foundation of mechanics principles for more than 50 years. Now in its new Sixth Edition, the text continues to help students develop their problem-solving skills with an extensive variety of highly interesting problems related to engineering design. In the new edition, more than 40% of the homework problems are new. There are also new sample problem and more photographs that link theory to application. To help students build necessary visualization and problem-solving skills, the text strongly emphasizes drawing free-body diagrams--the most important skill needed to solve mechanics problems.